2018
DOI: 10.1177/1358863x18760181
|View full text |Cite
|
Sign up to set email alerts
|

Increase in skin perfusion pressure predicts amputation-free survival after lower extremity bypass surgery for critical limb ischemia

Abstract: The objective of this study was to determine how postoperative skin perfusion pressure (SPP) as a measure of blood flow after revascularization affects limb prognosis in patients with critical limb ischemia (CLI). We retrospectively reviewed 223 consecutive bypass surgery cases performed in 192 patients with CLI during a 10-year period. SPP was measured 1-2 weeks before and after the procedure. An SPP of 40 mmHg was set as the cut-off value for revascularization. Patients were grouped according to their postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…For endpoints dependent upon macrovascular function, such as the likelihood of major amputation, limb salvage, and overall survival, the predictive ability of SPP is less consistent. While some studies 16 have demonstrated an association of post-procedural SPP to AFS, other studies, 15 including the present study by Yamamoto and colleagues, 14 have not. Such discrepancies reflect the challenge in predicting major amputation and AFS among a complex population with many factors influencing such outcomes.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…For endpoints dependent upon macrovascular function, such as the likelihood of major amputation, limb salvage, and overall survival, the predictive ability of SPP is less consistent. While some studies 16 have demonstrated an association of post-procedural SPP to AFS, other studies, 15 including the present study by Yamamoto and colleagues, 14 have not. Such discrepancies reflect the challenge in predicting major amputation and AFS among a complex population with many factors influencing such outcomes.…”
contrasting
confidence: 53%
“…In this edition of Vascular Medicine , Yamamoto and colleagues explore the utility of SPP in a real-world, single-center, retrospective experience of 192 Japanese patients with SPP assessment before and after 223 consecutive lower extremity bypass surgeries. 14 Patients with CLI, as confirmed by a SPP < 40 mmHg, were offered open surgical revascularization. Baseline SPP was indicated by the lower of a plantar and dorsal SPP measurement on the ipsilateral foot.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…54 In a study by Yamamoto et al, the authors have found that an increase in SPP of 20 mm Hg after bypass surgery was associated with better limb prognosis. 55 Novel noninvasive techniques include the oxygen-to-see method, which is an optical measuring technique that combines white light spectrometry and laser Doppler flowmetry, mapping oxygen saturation, relative hemoglobin, and blood flow in target tissues. More interestingly, indocyanine green fluorescence imaging (ICG-FI) enables the visualization of perfusion of the entire foot and quantifies the washout of ICG in the peripheral tissues.…”
Section: Risk Stratification Models and Time To Heal Predictors Aftermentioning
confidence: 99%
“…54 In a study by Yamamoto et al, the authors have found that an increase in SPP of ≥20 mm Hg after bypass surgery was associated with better limb prognosis. 55…”
Section: Introductionmentioning
confidence: 99%